Accountability, Complacency, or Obfuscation? An Analysis of the U.S. Military's Prevention and Response Efforts to Military Sexual Trauma. (12th September 2017) - González-Prats, Maria Carolina
Abstract : On December 3, 2015, Secretary of Defense Ashton Carter announced the end of the combat exclusion policy prohibiting women from serving in direct combat roles, regardless of the service branch or military occupation. For many, this represented the final barrier to women's opportunity for equality within the armed forces, since many jobs and promotions are tied to combat experience. However, this historically significant milestone is juxtaposed against a recurring problem for the military that threatens its state of readiness and national security: military sexual trauma (MST). This article explores the prevalence of sexual harassment and sexual assault in the U.S. military, and the misleading, and often contradictory, data provided by military officials and the Department of Defense. The argument presented here is that the obfuscation of MST data has ethical implications for public administration, as it negatively impacts any meaningful prevention, intervention, and reform efforts. At a time of emerging global threats and with less than 1% of the American public currently serving in the all-volunteer military, can the nation continue to risk remaining ignorant about these preventable crimes against its service members?